Visco-hypoelastic model of photo-polymerization process for small changes of temperature - Gambin, W. (Archives of Mechanics, 2010)
The aim of the paper is to propose a model for estimation of the shrinkage stress in photo-cured dental restorations. Up to now, the elastic and viscoelastic models of photo-curing process use an incremental approach with a large number of time steps, with a fixed Young’s modulus and viscosity within each of the time increments. The elastic approach with a stepped increasing Young’s modulus gives the stress values too high. On the other hand, the incremental viscoelastic approach requires long-lasting computations. In the present paper, a consistent model of the photo-curing process for the case of small temperature changes is proposed. The proposition bases on the Maxwell model, in which the Young’s modulus and the viscosity are continuous functions of time. The assumptions of the model follow from the dental practice, as well as from a physical nature of the process and from the rules of continuum mechanics. A performed incremental analysis of the process enables to formulate an integral model of the process, with an explicit rule for the shrinkage stress for 1D and 3D cases. The model has been tested for the material data of dental composite Clearfil F2. Results of the calculations coincide with the values of stresses measured in thin layers of Clearfil F2.